ADALIMUMAB: NEW OPPORTUNITIES OF RHEUMATOID ARTHRITIS TREATMENT - E.I. Alexeeva; A.O. Lisitsin; N.A. Karagulyan; O.L. Lomakina; S.I. Valieva; T.M. Bzarova; R.V. Denisova; E.Yu. Gudkova; A.M. Chomakhidze; K.B. Isaeva (Вопросы современной педиатрии)
This article presents the results of a trial, studying effectiveness and safety of adalimumab in treatment of 16 patients with different types of juvenile arthritis, refractory to standard immunosuppressive treatment and infliximab. The treatment with adalimumab provided the development of articular syndrome and uveitis remission, decreasing and normalization of laboratory indices of disease activity, lessening of disabling disorders rate, increase of quality of life in all patients. The tolerance to adalimumab was satisfactory: there was no any adverse event related to treatment.Key words: children, juvenile arthritis, treatment, uveitis, adalimumab.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):88-94)